Contemporary Economic Growth Models and Theories: A Literature Review - Ilkhom Sharipov (CES Working Papers, 2015)
One of the most important aspects of human development is the ability to have a decent standard of living. The secret of the "economic miracle" of many countries that have high standard of living, in fact, is simple and quite obvious. All these countries are characterized by high and sustained development of national economy, low unemployed population rate, growth of income and consumption. There is no doubt that economic growth leads to an increase in the wealth of the country as a whole, extending its potential in the fight against poverty, unemployment and solving other social problems. That is why a high level of economic growth is one of the main targets of economic policy in many countries around the world. This brief literature review discusses main existing theories and models of economic growth, its endogenous and exogenous aspects. The main purpose of this paper is to determine the current state of development of the economic growth theories and to determine their future directions of development.
Keywords: O40; E11; E12; E13; 330; economic growth; exogenous growth; endogenous growth